Acrobat X Pro - Hoffman, Michael J. (InfiniteSkills, 2011)
"In this Adobe Acrobat X video training course, expert author and trainer Michael Hoffman will show you that Acrobat X is capable of much more that being a simple PDF reader that most people use it for. You can create documents, forms, add interactivity, collaborate and publish your work for everybody to view. Starting with a review of the interface and toolbars, this video tutorial will teach you to get the most out of Adobe Acrobat X. You will learn the basics of creating PDFs, how to edit a PDF, combine documents, add or remove specific pages, and add interactivity to your PDFs. You will also learn how to create forms and manage the data from them, how to collaborate in your PDF documents, as well as methods of securing your PDFs. Finally you will learn how to publish your PDF to various outlets, from email, to web, as well as preparing it for professional printing. By the conclusion of this video training course on Adobe Acrobat X, you will be fully capable of creating, editing, and sharing your documents in PDF form. The author has included extensive working files to allow you to work alongside him as you learn."--Resource description page.